Pelatihan Pembuatan Camilan Sehat sebagai Inisiasi Wirausaha Rumahan pada Ibu Kader dan Ibu Balita di RW 03 Kelurahan Gandaria Utara: Training on Healthy Snack Production as an Initiative for Home-based Entrepreneurship for Health Cadres and Mothers of Toddlers in RW 03 Gandaria Utara Village - Ngadiarti, Iskari; Muntikah, Muntikah; Putri, Bintang Rizkia; Nixon, Aurasyifa Salsabila (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
One indirect cause of stunting is families' low purchasing power, which prevents them from providing sufficient food in sufficient quantity and quality. The provision of quality and affordable food is expected. The purpose of this community service activity is to train cadres and the mothers of stunting toddlers to make healthy food or snacks they can consume themselves and sell. This training begins with making healthy snacks, namely nuggets, for cadres at the North Gandaria Village Health Center. The method used was a lecture and demonstration of making healthy snacks, followed by providing materials to make at home and bringing them to the Puskesmas for assessment. The winning RW was asked to train mothers of stunted toddlers in their area. After that, skilled mothers of stunted toddlers were asked to join the cadre mothers to make their products, which were marketed once a week during every posyandu activity in all RWs in the North Gandaria Village Puskesmas area. During training and competitions for cadres and mothers of stunted toddlers, it became apparent that all mothers were happy and creative, coming up with various healthy snack variants made with protein and fruit. This activity provides benefits, namely the emergence of new entrepreneurs, the production of nuggets and healthy drinks for cadre mothers, in collaboration with mothers of toddlers, which indirectly increases cash for the smooth implementation of posyandu in their area.